Planning to provide the human book service in the libraries of Menoufia University - Tamer Daoud (Cybrarians Journal, 2018)
The scientific study being prepared by researcher Tamer Hanafi Dawoud, lecturer in the Department of Libraries and Information, Menoufia University, aims to plan the provision of book/human library services in the libraries of Menoufia University. This is one of the most important justifications for conducting this study, represented by the researcher’s desire to develop the service base of the university libraries, so that it includes new and non-typical types of information services, to which a large segment of the beneficiaries of the university library community (students) may respond, especially in light of the reluctance Notes about reading library resources. The researcher conducted a survey directed at the human base (human sources/books) to be used in providing the service, in order to measure their response to voluntary participation in activating and providing the service. The idea/initiative was appreciated by the majority of them (who are university professors in various human specializations). + Some trustworthy and experienced people known for their knowledge, morals, and attractive charisma.